Rotation of Stresses in French Wheel Tracking Test - Djenane, Mohamed; Demagh, Rafik; Hammoud, Farid (Salehan Institute of Higher Education, 2022)
The main function of a pavement is to distribute the traffic-induced load over its different layers. While the flexible pavement design methods are based on a linear elastic calculation, the real behavior of the different layers is highly non-linear and elastic. They can also, in some cases, be plastic and viscous. This research aims to develop a three-dimensional numerical model that is closely similar to the test FWTT conditions. The model will have a real geometry wheel footprint (rather than a rectangular shape). As a substitute for incremental loading, the wheel movement during its passage over the specimen will be simulated by a horizontal displacement. These important characteristics of the model represent the novelty and the major difference between the current research and previous studies. The current model, which is based on the finite elements method, uses Abaqus software and a viscoelastic constitutive model. The materials' viscoelastic properties have been described by the Prony series, also called the relaxation modulus, which is a function of time. This parameter can be defined in most computer-aided engineering (CAE) software. The procedure for calculating the Prony series from experimental data is explained. The results obtained agree with the stress signal amplitude, the stress rotation principal, and the total displacement rotation when the load approaches the node considered and located in the middle of the specimen.Â Doi: 10.28991/CEJ-2022-08-03-03 Full Text: PDF